STUDY OF WIND PROFILE VARIABILITY FOR DETERMINING THE EFFECTIVENESS OF HUB HEIGHT WIND TURBINE IN DIFFERENT TOPOGRAPHIC - Hikmah Rusmanansari, Arifatus
The vertical profile of wind in Indonesia has a different pattern because it is influenced by local conditions including topographic forms. Flat topography, hills, and cliff will produce different vertical profile patterns. To see the effect of topography on the vertical profile of the wind, the observation points in West Sulawesi were used as representatives of hilly topography and West Java for flat topography. Indirectly the vertical profile of the wind also affects the determination of the height of the wind turbine which involves several factors namely wind shear coefficient, turbulence intensity, and power output. Observation data starts from December 2017 to June 2018. The process of quality control of observational data is carried out first as verification. Then the analysis of climatological conditions of wind speed and direction at the observation point is used CCMP version 2. Calculation of wind shear coefficient, turbulence intensity, and power output are factors in determining the height of wind turbines. In addition, the calculation of the wind shear coefficient value will have an impact on the vertical shape of the wind that appears. During the month of observation, there were differences in wind vertical profile patterns in the two regions. Areas with hilly topography tend to have a variety of vertical wind profiles and have wind shear coefficient value that is two times smaller when compared to flat topography and greater turbulence intensity above 35%. However, the output power has almost the same value. If viewed from the three factors determining the effective height of the turbine, the reference of the wind turbine height in West Sulawesi is at least 100 m or more while the West Java area is 80 m high.